Origins of information visualization in corporate bullet points: an archaeology of the graphic configuration paradigm in data visualizations (1979–1995) - Ranoya, Guilherme; de Castro Andrade, Rafael (InfoDesign, 2024)
The present work seeks to highlight the origin of the current paradigm of data visualization design and the logic of creating charts and presentations, which emerged with the personal computer revolution. The initial digital tools developed for producing corporate communication artifacts were crucial in establishing the reasoning and production flow of visualizations up to the present day. Knowing beforehand that the origin of data visualization predates personal computing by centuries, it’s surprising that it is now entirely subject to models and guidelines originating from computer sciences. Through an investigation conducted with an archaeological method adapted to design artifacts, it is possible to understand the discontinuity and abrupt transformations experienced in the conventions and values of this practice. Through this methodological approach, along with the analysis of the productive mindset discourse and the available tools in this specific period, it becomes possible to explain the changes that aparted the craft of visualization artifacts from the domain of art and/or design, subjecting them to corporate sphere empowered by emerging arsenal of information technologies.